2014
DOI: 10.4306/pi.2014.11.2.143
|View full text |Cite
|
Sign up to set email alerts
|

Baduk (the Game of Go) Improved Cognitive Function and Brain Activity in Children with Attention Deficit Hyperactivity Disorder

Abstract: ObjectiveAttention deficit hyperactivity disorder (ADHD) symptoms are associated with the deficit in executive functions. Playing Go involves many aspect of cognitive function and we hypothesized that it would be effective for children with ADHD.MethodsSeventeen drug naïve children with ADHD and seventeen age and sex matched comparison subjects were participated. Participants played Go under the instructor's education for 2 hours/day, 5 days/week. Before and at the end of Go period, clinical symptoms, cognitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 48 publications
0
23
1
Order By: Relevance
“…Many cognitive training programs have been shown to improve cognitive abilities ( Diamond and Lee, 2011 ; Diamond, 2013 ). For instance, working memory training has been suggested to improve performance in untrained working memory ( Holmes et al, 2009 ); video-game training has been reported to improve performance in visual attention and executive control ( Strobach et al, 2012 ; Belchior et al, 2013 ); musical training and chess or go games playing that require a broad range of cognitive skills, have been found associated with superior performance in multiple cognitive tasks including working memory, executive control and reasoning ( Kim et al, 2014 ; Benz et al, 2016 ; Burgoyne et al, 2016 ; Sala et al, 2017 ). Moreover, all the above cognitive training programs have been reported to produce functional and structural changes in the brain that may provide a neurophysiological basis for the cognitive transfer ( Klingberg, 2010 ; Gong et al, 2015 ; Benz et al, 2016 ; Sohn et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many cognitive training programs have been shown to improve cognitive abilities ( Diamond and Lee, 2011 ; Diamond, 2013 ). For instance, working memory training has been suggested to improve performance in untrained working memory ( Holmes et al, 2009 ); video-game training has been reported to improve performance in visual attention and executive control ( Strobach et al, 2012 ; Belchior et al, 2013 ); musical training and chess or go games playing that require a broad range of cognitive skills, have been found associated with superior performance in multiple cognitive tasks including working memory, executive control and reasoning ( Kim et al, 2014 ; Benz et al, 2016 ; Burgoyne et al, 2016 ; Sala et al, 2017 ). Moreover, all the above cognitive training programs have been reported to produce functional and structural changes in the brain that may provide a neurophysiological basis for the cognitive transfer ( Klingberg, 2010 ; Gong et al, 2015 ; Benz et al, 2016 ; Sohn et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to functional differences, white matter studies have also revealed structural differences and stronger connectivity in regions associated with attentional control, working memory, and problem‐solving when trained in the game of “Go” (Lee et al., ). These results suggest that the neurocognitive load required to play “Go” may have therapeutic and advantageous effects for development (Kim et al., ; Newman, Hansen, & Gutierrez, ).…”
Section: Introductionmentioning
confidence: 94%
“…Thus parasympathetic fine-tuning, associated with safe environments, enables calm and subtle bidirectional brain–body communication and should facilitate appraisal of information in undelimited ways, to increase the learner’s cognitive engagement and optionality of response. It seems likely that a range of influences on executive functionality including physical movement ( Khalil et al, 2013 ; Rommel et al, 2013 ), musical training ( Kraus et al, 2014 ; Miendlarzewska and Trost, 2014 ; Fonseca-Mora et al, 2015 ; Francois et al, 2015 ), complex games ( Kim et al, 2014 ), and exposure to natural environments ( Taylor and Kuo, 2009 ) entail rhythmic or playful engagement with the learner’s autonomic arousal level, and these studies further highlight how brain functional domains interact in complex ways to produce lived and meaningful experience.…”
Section: Perspective Objective and Strategy Of The Ganementioning
confidence: 99%